Artificial Natural Selection: Can Supplemental Feeding Domesticate Mosquitoes and Control Mosquito-Borne Diseases? - Marc Egeth; Robert Kurzban (Evolutionary Psychology, 2012)
A new method is proposed for controlling mosquito-borne diseases. In particular, instead of trying to kill mosquitoes, we suggest provisioning them with food from artificial feeders. Because mosquito populations are frequently limited by ecological factors other than blood meals, such as the availability of egg-laying sites, feeding mosquitoes would not necessarily increase the total number of mosquitoes, but could reduce the number of human-drawn mosquito meals. Like mosquito traps, feeders could divert biting mosquitoes away from people by means of lures, but, after diversion, prevent subsequent human bites by satiating the mosquitoes instead of killing them. Mosquito feeders might reduce the problem of the evolution of resistance to control: in an ecology with mosquito feeders, which provide safe and abundant calories for adult female mosquitoes, there could be selection for preferring (rather than avoiding) feeders, which could eventually lead to a population of feeder-preferring mosquitoes. Artificial feeders also offer the chance to introduce novel elements into the mosquito diet, such as anti-malarial or other anti-parasitic agents. Feeders might directly reduce human bites and harnesses the power of natural selection by selectively favoring feeder-preferring (rather than trap-resistant) mosquitoes.